"A Matter Newly Seene": The Bishops' Bible, Matthew Parker, and Elizabethan Antiquarianism. Issue 2 (3rd July 2022) - Spillane, Harry
ABSTRACT : This essay examines Archbishop Matthew Parker's prefaces to the 1568 Bishops' Bible. It illustrates how these prefaces supported the attempts made by Parker (1504-75) to link the fledgling Elizabethan Church to the Anglo-Saxon Church. Particular attention is given to the use of the Venerable Bede (673/4-735) and King Alfred (848/49-99) as precedents for the existence of vernacular Bibles within the English Church. It is suggested that the prefaces can only be understood properly if they are seen as a part of Parker's antiquarian project and that, in turn, they develop our understanding of Parker's antiquarian methods and his construction of new histories for the English Church. Questions are also raised about the motives Parker had for printing some medieval works but not others, namely Bede's Ecclesiastical History . Ultimately, it is contended that the Bishops' Bible prefaces are an important, but hitherto overlooked, part of Parker's corpus of antiquarian works.